Optimizing Tilapia (Oreochromis niloticus) Growth through a Comparative Evaluation of EM4 and Homemade Probiotics in Pellets - Muhammad Izzudin Syaifullah; Satyantini, Woro Hastuti (Department of Aquaculture, 2024)
One alternative approach to facilitate the utilization of feed by tilapia is the addition of probiotic in feed. In this study, we compare the effects of commercial probiotic EM4 and homemade probiotics on tilapia growth. This research was conducted in PT. Sahaja Berkah Abadi at wonosalam, jawatimur, indonesia. The study was designed as a completely randomized design with 3 treatments and 4 replications, encompassing control group (C), commercial probiotics (G1), and homemade probiotic (G2). The commercial probiotics (G1) contained Rhodopseudomonas sp., Lactobacillus sp., Streptomyces sp., and Actinomycetes sp. while the homemade probiotic (G2) contained starter bacteria Lactobacillus casei and herbal plant such as ginger, curcuma, and tumeric. Parameters observed during the study included weight gain (WG), specific growth rate (SGR), and survival rate (SR). The results revealed that both G1 and G2 performed better than the control group. The weight gain for the control, G1, and G2 groups were 2.38±0.03 g, 3.09± 0.01 g, and 3.13 ± 0.03 g, respectively. Similarly, the specific growth rates for the control, G1, and G2 groups were 4.25±0.03%, 5.52± 0.02%, and 5.59 ± 0.03%, respectively, while the survival rate remained at 100% across all groups. The water quality in all treatments during maintenance met the standard requirements for tilapia, with temperatures ranging from 25.5 to 26.7 °C and pH levels between 6.7 and 6.9. These findings suggest that the probiotics incorporated in G2 present a cost-effective alternative to those in G1, offering a promising option for tilapia cultivation.